Preventive effect of probiotics supplementation on occurrence of gestational diabetes mellitus: A systematic review and meta-analysis of randomized controlled trials - Pakmehr, Azin; Ejtahed, Hanieh-Sadat; Shirzad, Nooshin; Hemmatabadi, Mahboobeh; Farhat, Sara; Larijani, Bagher (Frontiers in Medicine, 2022)
Background: Gestational diabetes mellitus (GDM) is a health challenge during pregnancy and is associated with adverse effects. Dysbiosis of the gut microbiota may play a role in developing inflammation and insulin resistance observed in GDM. Probiotics are supposed to be influential in preventing GDM since they can alter the composition of microbiota in the intestine. Despite the existing studies on the therapeutic effects of probiotics in women with GDM, in this study we aim to systematically review and meta-analyze the results of randomized control trials (RCTs) on the beneficial effects of probiotics supplements on the prevention of GDM in healthy pregnant women. Methods: Web of science, Scopus and PubMed databases were searched via a precise strategy to gather RCTs related to our study. Duplication removal, screening and data extraction were conducted by two researchers, independently. Quality assessment of eligible studies was conducted by Cochrane risk of bias tool. Meta-analysis was conducted using the random effects model due to substantial heterogeneity among studies. Results: Ten articles met our eligibility criteria from our initial search of 451 articles. 2921 participants without previously diagnosed glucose disturbance were included in our analysis. Probiotics reduced GDM incidence by 33% (RR=0.67, 95% CI: 0.47, 0.95), while greater effect was detected in trials using multiple-strains prpbiotics (RR=0.65, 95% CI: 0.42, 0.99). We did not detect any significant benefits or harms related to probiotics supplements on secondary outcomes including GDM related infantile and maternal complications including preeclampsia, caesarian section, mothers’ weight gain during pregnancy, prematurity, macrosomia, hypoglycemia, NICU admission and birth weight. Conclusion: Probiotics supplementation may reduce the incidence of GDM and help control glucose parameters in pregnant women. Further studies are warranted regarding the GDM-related maternal and infantile complications.